PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN KOMITMEN GURU TERHADAP KINERJA GURU MA MUHAMMADIYAH 1 PAKIS DUREN - Setyocahyono, Wahyungesthi; Bukhori, Mohammad; Dewi, Widi (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
ABSTRACT The teacher is one of the most important actors and is the spearhead of education. Teachers are required to provide services according to standards, so that they are expected to produce more qualified human resources. The design in this study uses a quantitative approach with the Causality method. The population used is all teachers of MA Muhammadiyah 1 Pakis Duren Banyuwangi with a total of 33 respondents, using total sampling. Based on the results of statistical test analysis using several tests, such as the F test, the results showed that the F value was 6.442 with a significance level of 0.002 or less than 0.05. Therefore, it can be concluded that Organizational Culture, Work Motivation and Work Commitment simultaneously affect the performance of MA Muhammadiyah 1 Pakis Duren teachers. Individually, the effect of Organizational Culture, Work Motivation and Work Commitment variables was measured using the t-test with the results that there were: 1) Not significant between the Organizational Culture variables on the Teacher Performance variable, 2) The significant between the Work Motivation variable on the Teacher Performance variable was 0.573, and 3) There is no significant difference between the Performance Commitment variable and the Teacher Performance.